English for European Communication and Tourism: Focus on Pragmatic Competence - Klimczak-Pawlak, Agata (Research in Language, 2019)
Pragmatic competence in L2 English is claimed here to be crucial for successful communication in a variety of communicative contexts across Europe. However, due to language background, cultural and identity differences among users of English, there is a need for reflection and data-driven examination of how the language is used in specific situations. This paper adopts a cross-cultural perspective on the study of the use of English in the European Union with focus on its role in tourism. The role of English as the language of communication in Europe is discussed, followed by a proposal as to the way in which its actual usage can be studied. The data-driven approach to pragmatic behavior is advocated as the basis for the development of pragmatic competence in learners of English with focus on those who wish to engage in tourism.